204k views
1 vote
Please answer. Thanksss

Please answer. Thanksss-example-1
User RAthus
by
5.4k points

2 Answers

4 votes

Answer:

No, No, Yes, Yes

Explanation:

We can simply substitute the pairs as x and y in the equation:

(5, 0)

7*5 + 5*0 = 35 + 0 = 35


35 \\e 9

(-4, -3)

7*(-4) + 5*(-3) = -28 - 15 = -43


-43 \\e 9

(2, -1)

7*2 + 5*(-1) = 14 - 5 = 9


9 =9

(-3, 6)

7*(-3) + 5*6 = -21 + 30 = 9


9 = 9

User Sadegh J
by
5.1k points
3 votes

Answer:

1. no

2. no

3. yes

4.yes

Explanation:

hope this helped

User Ahmad Yoosofan
by
5.6k points